Pluralismo giuridico e pratica giuridica indigena: il caso dei Guaranì del Chaco Boliviano - Scionti, Francesca (EtnoAntropologia, 2017)
This article ethnographically explores the form and the content of juridical practices of Guarani people living in the Capitanías of Charagua Norte and Alto Isoso, Bolivia. Starting from the Bolivian legal pluralism main field and through the analysis of some juridical case study, I answer some questions about how the Guarani people act and interpret the legal field in a plural legal context. I argue that such guarani people practice is both rooted in an interlegal field of sense and meaning and product of a legal and political strategy useful to hide and protect the indigenous juridical habitus.